Factors associated with reinfection of syphilis in reference centers for sexually transmitted infections - Valéria Correa de Almeida; Maria Rita Donalisio; Ricardo Cordeiro
ABSTRACT OBJECTIVE We aim to analyze trend of syphilis and factors associated with recurrent episodes of syphilis among adults and adolescents attended in a STI/AIDS reference centers in Campinas, state of São Paulo, 2004 to 2012. METHODS Medical records, pharmacy data, and notification database were accessed to analyze trends of syphilis and sociodemographic, epidemiological and clinical variables associated with reinfection of syphilis. After univariate analysis, a hierarchical logistic regression model was adjusted to analyze variables associated with more than one episode of syphilis (dependent variable). First step (sex, age, and years of schooling) were tested and in the second, epidemiological and clinical variables. RESULTS A total of 1,009 episodes of syphilis were identified among 860 adolescents and adults, 117 individuals (13.6%) presented with more than one episode of syphilis. Factors associated with more than one episode of syphilis were sex (male) (OR = 4.28; 95%CI 1.31-14.0), age (OR = 1.02; 95%CI 1.00-1.04), homosexual/bisexual orientation (OR = 2.29; 95%CI 1.22-4.32), HIV coinfection (OR = 3.54; 95%CI 2.22-5.63), and absence of STI symptoms at the time of syphilis diagnostic (OR = 1.70; 95%CI 1.03-2.80). CONCLUSIONS The number of cases of syphilis and proportion in relation to STI increased in recent years in a specific population attended in a STI/AIDS reference centers in Campinas. Association with HIV, homosexual/bisexual orientation and the silent clinical characteristic of cases confirm the necessity to implement more aggressive strategies to prevent the occurrence of syphilis and other STI in specific populations with higher disease risk.